Investigation of 60Co BEBIG High Dose Rate Brachytherapy Dose Distribution in Different Media Using GEANT4 Monte Carlo Simulation - Jayakody, M.; Jeyasugiththan, J.; Peterson, S.W.; Rajasooriyar, C.; Chougule, A. (University of Colombo, 2024)
High Dose Rate (HDR) Brachytherapy (BT) using 60Co source, uses radioactive sources placed inside patient's body, targeting tumour regions. Consequently, treatment planning is the main step in HDR-BT, which relies on the computer algorithm 'Treatment Planning System' (TPS). The current approach to TPS is based on the American Association of Physicists in Medicine (AAPM) Task Group No. 43 (TG-43) formalism. A major ...
Keywords: HDR Brachytherapy; 60Co; GEANT4 Simulation; Dose Distribution; Tissue Heterogeneity